Word Structure Of Negative Prefixes In The “Wrecker” Novel - Prasetyo, Andie; Rajeg, Gede Primahadi Wijaya; Indriani, Ketut Santi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Negation is an essential aspect of communication. In English, one common morphological strategy to express negation is by attaching negative prefixes to base forms. This study analyses the morphological structure of words containing negative prefixes found in the Wrecker novel (Hiaasen 2023), based on the framework proposed by Plag (2023). In the novel, we identified a total of 89 unique words containing negative prefixes; words with the prefix un- is the most prevalent. The classification of these words reveals two distinct structural patterns (that are represented as tree diagram). The first pattern consists of a root word combined with a negative prefix, negating its meaning without altering its grammatical category. The second pattern involves more complex words, where two to three morphemes are used along with a suffix, modifying both the meaning and the word class. The findings contributed to enhance understanding of morphological patterns in literary texts, encouraging future studies to broaden the scope by analyzing additional works across various genres and authors to determine whether similar structures might persist or vary in different contexts.